Electrochemical reduction of azidophenyl-deoxynucleoside conjugates at mercury surface. (1st January 2018) - Daňhel, Aleš; Trošanová, Zuzana; Balintová, Jana; Simonová, Anna; Pospíšil, Lubomír; Cvačka, Josef; Hocek, Michal; Fojta, Miroslav
Abstract: Azidophenyl-linked nucleotides were previously used for redox-labelling of DNA. Lack of information about electrochemical behavior of aromatic azides in aqueous media and more complex reduction mechanism from to-date presented straightforward two electron reduction to corresponding amines and diatomic nitrogen led us to study the electrochemical reduction process more in detail. Model potassium 4-azidophenyltrifluoroborate (AzPTFB) and the corresponding AzP-linked nucleosides, 7-(4-azidophenyl)-7-deaza-2′-deoxyadenosine (dA AzP ) and 5-(4-azidophenyl)-2′-deoxycytidine (dC AzP ), were studied using DC and AC polarography, cyclic voltammetry and electrochemical impedance spectroscopy at dropping mercury electrode or at hanging mercury drop electrode in aqueous buffers. Electrochemical reduction of the azidophenyl conjugates is influenced by pH. Even if electrolysis of AzPTFB and dA AzP at mercury pool confirmed consumption of two electrons per molecule, simple two electron reduction of azide group to amine proceed only in acid electrolytes (pH < 2). Preparative chromatography of the solution obtained after dA AzP electrolysis in ammonium formate-phosphate buffer pH 6.9 and potassium chloride-phosphate buffer pH 6.9 revealed also presence of formylaminophenyl- and phenyl-derivatives. Nevertheless, intermediates such as dimers of the amine compounds and/or hydroxylamine-derivatives, which yield characteristic anodic peak in CV, are transiently formed. The intermediates are finally transformed to amines via reduction at more negative potentials. According to the results, mechanism of dA Azp electrochemical reduction is proposed in this work. Highlights: Electrochemistry of 4-azidophenyl conjugates was studied at HMDE in aqueous media. AzPTFB, dA AzP and dA Azp -triphosphate are reduced by 6, 2 and 3 electrons per molecule at mercury pool. Products of the dA AzP electrolysis were isolated by RP-HPLC and identified by HRMS and 1 H and 13 C NMR. Phenyl- and formylaminophenyl-conjugates are produced besides anticipated aminophenyl-dA conjugate. Mechanism of dA Azp electrochemical reduction was proposed.